Digital-Based Consumer Loyalty Development in realizing an Independent Economy at PSAA PU3 Ceger - Richy Wijaya; Dyah Astarini; Aji Kusuma Wijaya (CV. AFDIFAL MAJU BERKAH, 2025)
Social institutions play a vital role in supporting underprivileged children and teenagers by offering guidance and essential services. Recognizing that the youth represent the future of our nation and are integral to its progress, it's imperative to empower these institutions. The orphanage, traditionally seen as a financial burden, now faces the imperative of achieving socio-economic independence. In response to this challenge, the Kedaireka grant recipient team has initiated the Green-Techno Sociopreneur Livestock Magot project to bolster the economic autonomy of social institutions. As of October 20, 2022, maggot cultivation has commenced in three social institutions in DKI Jakarta. However, during the assessment phase, it was noted that the residents and administrators of one of the participating institutions, PSAA 3 Ceger, lacked the capability to conduct effective marketing activities. To address this issue, the Community Service team from the Faculty of Economics and Business at Trisakti University intends to organize outreach programs aimed at enhancing the marketing skills of the residents and administrators of PSAA 3 Ceger. The objective of this Community Service project is to impart knowledge and understanding of building consumer loyalty through digital technologies. Participants will receive guidance in content creation, setting up e-commerce platforms, crafting captions, and implementing other digital marketing strategies. A crucial aspect of this initiative is ongoing sustainability monitoring, which will be undertaken by the student team and further developed in a dedicated program.